2011
DOI: 10.7763/ijssh.2011.v1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Burnout Dimension on Employees' Performance

Abstract: The psychological sensitivity in each job is a good stage for stress and jobs accidents, so prevention of job burnout as the main issue of public healthcare is under the spotlight. The aim of the current article is to determine job burnout and its relation with the components of job burnout in the performance of the bank personnel. The Current research is practical and its method is united and post event. The Statistical society includes all personnel of Mellat Bank which is about 500 People in Golestan provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
1
27
1
7
Order By: Relevance
“…Hasil penelitian Alinuari (2012) menunjukkan hubungan masa kerja terhadap kejenuhan adalah semakin lama masa kerja seorang pegawai maka kejenuhan kerja semakin meningkat. Pegawai yang mengalami kejenuhan kerja akan mengakibatkan kinerja (job performance) yang menurun sehingga output kerja mereka dapat menurun pula (Gorji, 2011).…”
Section: Pengaruh Masa Kerja Terhadap Kualitas Laporan Keuangan Pemerunclassified
“…Hasil penelitian Alinuari (2012) menunjukkan hubungan masa kerja terhadap kejenuhan adalah semakin lama masa kerja seorang pegawai maka kejenuhan kerja semakin meningkat. Pegawai yang mengalami kejenuhan kerja akan mengakibatkan kinerja (job performance) yang menurun sehingga output kerja mereka dapat menurun pula (Gorji, 2011).…”
Section: Pengaruh Masa Kerja Terhadap Kualitas Laporan Keuangan Pemerunclassified
“…The results of the survey on the emotional exhaustion dimension of burnout suggest that it had a moderate impact on employees at the King Abdul-Aziz University. A similar study by Gorji (2011) also noted high-level emotional exhaustion as a principal aspect of burnout in addition to depersonalization. According to the outcomes, the highest ranked factors that were associated with emotional exhaustion were job-related frustration, emotional exhaustion resulting from work, and emotional drain.…”
Section: Emotional Exhaustionmentioning
confidence: 60%
“…The MBI-GS multidimensional approach implies that it may be more effective to consider how to reduce the likelihood of emotional exhaustion, or to prevent the tendency to depersonalize, or to enhance one's sense of accomplishment, rather than to use a more general stress reduction approach (Maslach & Schaufeli,1993). Gorji(2011) investigated the relationship between the impact of job burnout dimension on employees" performance‫‬ of 250 bank workersin Golestan region in Iran. The findings have shown that in addition to the high amount of job burnout through personnel's, other characteristics like passionate tiredness and depersonalization has a certain reverse effect on the performance of an individual.…”
Section: Measurement Of Burnoutmentioning
confidence: 99%
See 2 more Smart Citations